2002
DOI: 10.1046/j.1365-8711.2002.05682.x
|View full text |Cite
|
Sign up to set email alerts
|

A search for 6Li in stars with planets

Abstract: Using very high-resolution (R∼ 125,000) and high quality (S/N ≥ 350) spectra, we have searched for 6 Li in stars hosting extra-solar planets. From detailed profile-fitting of the Li i resonance line at 6707.7Å, we find no significant amount of 6 Li relative to the 7 Li for any of 8 planet bearing stars ( 6 Li/ 7 Li ≤ 0.0 -0.03 ) with a strong Li i lines. In particular, we do not confirm the presence of 6 Li with 6 Li/ 7 Li = 0.13 reported by Israelian et al.(2001) for HD 82943, a star with two known planets. S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
145
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(159 citation statements)
references
References 28 publications
10
145
4
Order By: Relevance
“…Israelian et al (2003) claimed the presence of a notable amount of 6 Li in the atmosphere of the planet host HD 82943. Yet Reddy et al (2002) did not find 6 Li in several of the eight stars that were identified in the literature as possible recipients of accreted terrestrial material, in addition to the star HD 219542 A, the planetless primary of a binary. Thus, in spite of a number of studies devoted to this topic, there is no consensus that SWP exhibit a decreased abundance distribution when compared to stars without planets, meaning the presence of planets may, or may not, affect the abundance or processing of lithium in stellar atmospheres.…”
Section: Introductionmentioning
confidence: 88%
“…Israelian et al (2003) claimed the presence of a notable amount of 6 Li in the atmosphere of the planet host HD 82943. Yet Reddy et al (2002) did not find 6 Li in several of the eight stars that were identified in the literature as possible recipients of accreted terrestrial material, in addition to the star HD 219542 A, the planetless primary of a binary. Thus, in spite of a number of studies devoted to this topic, there is no consensus that SWP exhibit a decreased abundance distribution when compared to stars without planets, meaning the presence of planets may, or may not, affect the abundance or processing of lithium in stellar atmospheres.…”
Section: Introductionmentioning
confidence: 88%
“…For the former, we adopted the Reddy et al (2002) hyperfine structure. We also added to the linelist the two Fe I and Ti I lines at 6707.433 Å and 6708.125 Å, respectively, listed in Gonzalez et al (2009, hereafter G09).…”
Section: Chemical Abundance Analysismentioning
confidence: 99%
“…3 using the abundances given in Lecureur et al (2007). The log gf value for Ti I line at 6708.025 Å was modified from that adopted by Reddy et al (2002) as well as both V I lines at 6708.125 Å and 6708.280 Å. The final, calibrated atomic lines used in the synthesis are listed in Table 2.…”
Section: Linelistsmentioning
confidence: 99%